Trade-off or synergy? The impacts of coal energy consumption on compound system vulnerability: A perspective from coal resource base assessment - Zhaorui Jing; Xiangyu Min; Sijia Li; Junying Li; Wen Song (Ecological Indicators)
No fundamental conflict exists between resource supply and ecological protection. But the combined pressures of economic development and carbon neutrality may drive a sharp disparity in the sustainability of ecological function enhancement across such the resources regions. Here, we systematically assess the composite relationship between capacity utilization and systems vulnerability of the coal base in northern Shanxi Province, verify the trade-off /synergy driving mechanism of ‘Energy saving and emission reduction’ in coal resource-based city. We found that overcapacity issues emerged in most areas, especially in the eastern-southeast-southern region. Spatial heterogeneity in the distribution of system trade-offs and synergies was noted in the North Shanxi Coal Base. There has been a shift from synergies to trade-offs in the overall scenario. Across spatial–temporal changes, the dominance was observed in bundles involving ecosystem vulnerability, social system vulnerability-ecosystem vulnerability, and carbon emissions-economic system vulnerability. Coal base should formulate adaptive policies based on the stage of development. The management partition will be divided into five zones and the capacity reduction trajectory into advancing, developmental, and stable phases, aims to ensure national energy security and foster sustainable coordinated development in the region.